MODIFIKASI Centrifuge DILENGKAPI SISTEM PENDETEKSI KETIDAKSEIMBANGAN SENTRIFUGASI BERBASIS ARDUINO - Kusnadi, Kusnadi; Persadha, Galih; Mayasari, Hikmah; Rasyid, Hendra (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
In the laboratory, a device is needed that is able to separate suspended particles in liquids according to their particle size and density. Centrifuge is the separation of blood and other body fluids such as urine, in certain cases it is necessary to separate its constituent components to facilitate the examination process. Centrifugation balance is a critical aspect of its operation. Mass imbalances in the rotor can cause vibration, excessive noise, and even damage to the tool. Therefore, the development of a centrifugation imbalance detection system is an important step to identify and address imbalances. Rotation imbalances can result in sample holder rupture, centrifuge damage, and sample contamination. The factors that affect the rotational balance and vibration of the centrifuge are the balance of the sample position and the number of samples. The method used in the research is Research and Development. Test results from field data for power supply voltage of 12.21 Vdc with an error accuracy of 1.75 %. In the DC to DC Buck Converter test, the average voltage is measured at 5.005 Vdc, the error accuracy is 0.1 %. In the Arduino Uno pin test, the average voltage measured is 5.005 Vdc, the accuracy error is 0.1 %. In the centrifuge time test, a comparison of 15.02 minutes was obtained, with an error accuracy of 02 seconds, and an error accuracy of 0.2 %. The feasibility test of the tool differs samples from 1 ml to 4 ml and speeds from 1000 RPM to 4000 RPM, the feasibility test includes validation assessments, function tests, and material validators are obtained 100 % and 88 %, meaning that this tool is very feasible to use.